Segmentasi produk dalam dunia pendidikan sekolah dasar - Firdaus, Muhammad Nur Kholilul; Rahmadiani, Rizza; Gempawan, Fitra Jaya; Refaza, Alink Kayani; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
Product segmentation in the world of primary school education is the process of dividing the primary school education market into several different groups based on customer characteristics, needs and preferences. This product segmentation can help educational institutions to be more effective in designing, marketing and producing products or services that suit the needs of various market segments. The aim of this research is to provide a study of the meaning, objectives and examples of product segmentation in the world of elementary school education. This research uses a literature study method obtained from problem identification to analysis where the results of this research show that product segmentation can be done by selling materials and tools for learning and assisting in managing the welfare of cooperatives within the institution.